Emergent canine visceral leishmaniasis in Argentina: Comparative diagnostics and relevance to proliferation of human disease. - Kyoko Fujisawa; Charlotte Silcott-Niles; Poppy Simonson; Daniela Lamattina; Cristian A Humeres; Tapan Bhattacharyya; Pascal Mertens; Caroline Thunissen; Victoria O'Rourke; Magdalena Pańczuk; James A Whitworth; Oscar Daniel Salomón; et al. (PLoS Neglected Tropical Diseases)
Background Visceral leishmaniasis (VL) is a zoonotic protozoal vector-borne disease that is a major public health challenge. In Argentina, canine (CVL) and human visceral leishmaniasis (HVL) have recently emerged. There is a lack of standardised diagnostic tests for CVL, which hinders control of CVL and HVL. Methodology/principal findings Sampling was carried out in Puerto Iguazú, Argentina, comprising 190 asymptomatic, oligosymptomatic and polysymptomatic dogs. The following diagnostics were applied: microscopy of lymph node aspirate (LNA); three immunochromatographic rapid diagnostic tests (RDTs), prototype rK28-ICT, rK39-ICT (both Coris BioConcept), commercial rK39 (InBios); ELISA for IgG, IgG1 and IgG2, against rK28, rK39 or crude lysate antigen. DNA detection and analysis, with 30 dogs, was of the ITS1 region using skin samples, and loop-mediated isothermal amplification (LAMP; Eiken Loopamp) of buffy coat, skin scrape or LNA. 15.4% of dogs were positive by LNA microscopy. The rK28 RDT had higher seropositivity rate (61%) than either a prototype rK39 RDT (31.4%) or commercial rK39 RDT (18.8%), without cross-reactivity with six other pathogens. IgG anti-rK39 ELISA antibody titres, but not IgG2, were positively correlated with number of clinical signs. LAMP with LNA had a higher positivity rate than PCR; buffy coat sampling was more sensitive than skin scrape. ITS1 confirmed Leishmania (Leishmania) infantum as the agent of CVL. Leishmania (Viannia) spp. was detected in skin samples from two dogs, compatible with Leishmania (Viannia) braziliensis. Conclusions/significance Seroprevalence confirmed rapid increase in CVL in Puerto Iguazú. The rK28 RDT test potentially has great value for improved point-of-care diagnosis. Given cost reduction and accessibility, commercial LAMP may be applicable to buffy coat. RDT biomarkers of CVL clinical status are required to combat spread of CVL and HVL. The presence of Viannia, perhaps as an agent of human mucocutaneous leishmaniasis (MCL), highlights the need for vigilance and surveillance.